Peningkatan Nilai Tambah Produk Jahe Bagi Masyarakat Murtajih Pamekasan dalam Mendukung One Village One Product - Hidayat, Khoirul; Firmansyah, R. Arief; Indarto, Cahyo; Asfan, Dian Farida; Fakhry, M (Proceedings of Annual Conference on Community Engagement, 2022)
Murtajih village is one of the villages in Pademawu District, Pamekasan Regency. Based on BPS data, the production of ginger in Pamekasan Regency in 2018-2020 was 2,114,765kg, 1,521,883kg, and 179,454kg. Therefore, it is necessary to carry out community empowerment activities in Murtajih Village to increase the added value of ginger products in supporting one village one product. The purpose of this activity is to provide added value for the community and produce processed ginger products as the flagship product. The approach method used in this community empowerment activity is Participatory Rural Appraisal (PRA). The results of community empowerment by utilizing ginger as a soft candy and hard candy based on the Hayami method have added values of 44.66% and 54.308%. The community well attends the workshop activities for making ginger products. It can be seen from the results of making products carried out by the community by has been given.